SENP3/FIS1-regulated PFC neural mitochondrial fragmentation underlies the mechanism of electroacupuncture attenuating depressive behavior in CUMS mice - Lai, Shaoda; Qiu, Xiaoke; Lin, Peilin; Wu, Jiayi; Li, Feifei; Lai, Ningjing; Li, Xin; Tu, Ting; Zhang, Jiping; Huang, Yong; Zhang, Zhinan (Frontiers in Psychiatry, 2026)
ObjectiveElectroacupuncture (EA) is a common alternative treatment for depression, but its underlying mechanism remains unclear. Research suggests that its therapeutic effect may involve reducing SENP3/FIS1-regulated mitochondrial fragmentation, thereby mitigating neuronal damage in the prefrontal cortex. This study aimed to evaluate the efficacy of EA at Baihui (GV20) and Yintang (GV29) on SENP3/FIS1-regulated mitochondrial fragmentation in prefrontal cortex neurons of depressive animals.MethodsTwenty-eight 6-8-week-old male C57BL/6 mice were randomly divided into normal control, depression, and EA groups. Following depression modeling, the EA group received EA at GV20 and GV29. The effects of EA on neuronal mitochondrial fragmentation and the SENP3/FIS1 pathway were evaluated using transmission electron microscopy, western blotting, and immunofluorescence assays.ResultsEA at GV20 and GV29 notably reduced depression-like behaviors in animals and exerted neuroprotective effects on prefrontal cortical neurons. It also inhibited FIS1-mediated mitochondrial fragmentation in the prefrontal cortex and enhanced SUMOylation. Further investigation of SENP3, the key regulatory enzyme for FIS1 SUMOylation, revealed that EA downregulated the SENP3-FIS1 interaction.ConclusionsThese evidences suggested that the antidepressant effects of EA may involve modulation of mitochondrial fragmentation regulated by the SENP3/FIS1 pathway in prefrontal cortex neurons.